Scoping Review of Critical Thinking Literature in Healthcare Education. Issue 1 (3rd January 2023) - Berg, Christine; Philipp, Rachel; Taff, Steven D.
Abstract: Critical thinking is the process of analyzing and evaluating thinking to make decisions. Critical thinking exposes assumptions, biases, and beliefs that influence clinical reasoning. This scoping review sought to explore instructional approaches for advancing students' critical thinking in healthcare education. Through analysis of 15 articles, no common definition of critical thinking emerged, nor consensus found on measurement or instructional methods. Some alternative instructional methods such as case-based learning, reflective guided questions, and multiple case exposures, when compared to lecture, did significantly impact learner critical thinking. To determine if critical thinking is an instructional method that would impact implicit biases and healthcare outcomes, five author recommendations are offered from gaps in the existing literature to provide a pathway for future research. To effectively prepare students for clinical practice, long term outcomes are necessary to assess if critical thinking skills can be taught and become part of a professional growth mindset.